AWARENESS OF THE THREAT TO THE HEALTH OF BEHAVIORAL RISK FACTORS FOR NONCOMMUNICABLE DISEASES BY FUTURE TEACHERS - Kalynychenko I.О.; Gulich, M.P.; Petrenko, O.D.; Liubarska, L.S.; Latina, H.O. (World of Medicine and Biology, 2023)
Recently, worsening of youth’s health, taking into account the vulnerability of growing and developing organism to the influence of risk factors for chronic noncommunicable diseases has been of a significant concern. The purpose of research was to determine students’ awareness of behavioral risk factors for the most threatening pathology of today and the role of a healthy lifestyle as a basis for preventing development of noncommunicable diseases. In order to achieve this goal 216 students of Sumy State Pedagogical University named after A. S. Makarenko were interviewed. A specially designed questionnaire was used. A high level of students’ knowledge and awareness of the main factors for noncommunicable diseases development was established. However, 16.3 % of students do not realize the importance of rational nutrition, 24.2 % – the optimal level of physical activity, 26.9 % – the danger of drinking alcoholic beverages; 42.8 % of youth regularly drink alcoholic, low-alcoholic beverages and beer, 26.5 % of students are unaware of the dangers of smoking. 11.6 % of surveyed have excess body weight, with 25.5 % of overweight among boys and 7.7 % – among girls. The priority of ways of obtaining information on risk factors of chronic noncommunicable diseases by youth was established.